An Exploration Study of Self-disclosure Communicative Strategies to Enact Friendship in Facebook Wall Posts - Ying, Lai Yuh; Thai, Yap Ngee; Sathivellu, Mohd Faiz (International Review of Management and Marketing, 2016)
Ever since the Facebook established, friending has become an easy thing as people take a simple click to bridge a connection. To connect with their friends, Facebook respondents disclosed information about themselves by posting messages on Facebook wall posts. The contents of wall post messages are more to disclose Facebook respondents' aspects of life. The initiative of Facebook respondents to share the happenings in their life with their Facebook friends is to maintain established virtual relationship as connecting friends through Facebook is free of charge and easy to reach. Thus, this study aims to explore the types of communicative strategies and the ways these communicative strategies used to maintain friendship online. This study can provide a better understand of self-disclosure as a behaviour category for enacting friendship in Facebook. Facebook posted messages from the participants' Facebook profiles were collected in one year time. This is qualitative case study. Content analysis was used to analyse posted messages. The posted messages were then categorised into types of communicative strategies in self-disclosure. The majority of the posted messages are self story-telling through state and action statements and affective statement. The Facebook users act as story-tellers were noted as they describe about their personal details and experience as a form of self-disclosure to increase the feeling of connecting with their Facebook friends. Keywords: Self-disclosure, Communicative strategies, Friendship, Facebook JEL Classifications: L86, I31